A COMPARATIVE STUDY BETWEEN GROUP DISCUSSION AND THINK PAIR SHARE STRATEGY TO ENHANCE STUDENTS’ SPEAKING ABILITY - Sri Wahyuni (English Education Department, 2019)
The aim of this study is to find out if there is any significant difference in students’ ability enhancement between those who were taught using Group Discussion strategy and those who were taught using Think Pair Share strategy. This study is a quantitative research method using comparative design by using pre-test and post-test. This study was designed to find out the answer to the following question: Is there any significant difference in students’ speaking ability enhancement between those who were taught by using Group Discussion strategy and those who were taught using Think-Pair-Share strategy. The sample of this study were two classes of grade X SMA Inshafuddi Banda Aceh. Grade X IPA 1 was taught using Group Discussion and grade X IPS were taught using Think-Pair-Share. The instrument used for this study was a speaking test, which contained a Congratulation topic. The result of this study showed from the mean score that both classes had an enhancement in their speaking ability. In addition, there was no significant difference between those who were taught using Group Discussion and those who were taught using Think Pair share strategy. However, it meant that both strategies were efficient in enhancing students’ speaking ability.